EKONOMI POLITIK PENDANAAN PENDIDIKAN ISLAM: ANALISIS ALOKASI DANA BOS MADRASAH 2015-2025 - Rida Putri (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study analyzes the allocation patterns of the BOS (School Operational Assistance) Fund for Madrasahs from 2015 to 2025 through a political economy lens. Employing a sequential explanatory mixed-methods approach, it combines quantitative analysis of secondary data from the Ministry of Religious Affairs with in-depth interviews involving 30 stakeholders across two key provinces (West Java, West Nusa Tenggara). The findings reveal significant disparities in fund distribution, influenced not solely by objective needs but also by electoral political interests. The concentration of funds in regions aligned with ruling party strongholds and spending surges in electoral years (e.g., 2018 and 2023) highlight systemic politicization. While certain regions saw improvements in madrasah infrastructure, the overall impact on teaching quality particularly in underdeveloped areas remains limited. This study recommends a restructured allocation formula based on real needs, local fiscal capacity, and institutional performance. Additionally, it proposes the establishment of an independent body to depoliticize Islamic education funding. The findings aim to guide policymakers in crafting a more equitable, evidence-based, and transparent budget allocation framework for religious education.